Plant traits affect vertical accretion of salt marshes. (5th October 2022) - Bass, Julia; Granse, Dirk; Hache, Ingo; Jensen, Kai; Karius, Volker; Minden, Vanessa; Stock, Martin; Suchrow, Sigrid; Kleyer, Michael
Abstract: The current climate crisis is associated with rising sea levels, which raises the concerning prospect of losing coastal ecosystems, such as salt marshes. Where inland migration is impossible, salt marshes will only persist if their vertical accretion exceeds the rate of sea-level rise. Positive vertical accretion is mainly driven by sedimentation, whereas negative vertical accretion is driven by erosion and soil compaction, among others. These processes can be influenced by abiotic and biotic factors. The biotic factors, best described by plant functional traits of the salt-marsh vegetation, are, however, not well understood. We assembled a large dataset of 336 plots with vertical accretion time series and plant abundances and coupled it with trait data from salt marsh species of the German Wadden Sea, covering natural unmanaged, anthropogenic unmanaged, and grazed marshes. By using multiple logistic regression analyses, we studied the effects of plant functional traits and distance to the marsh edge on vertical accretion. Mean vertical accretion was in the range of recent sea level rise, except for plots on elevated grazed marshes. There were, however, pronounced local differences in vertical accretion. Positive accretion increased with distance to marsh edge and increasing leaf and stem roughness, described by specific stem length, canopy height, stem mass, leaf mass and leaf area. Except on grazed marshes, leaf traits contributed more strongly to the explanation of positive accretion than stem traits. Negative accretion by e.g., erosion was facilitated by low specific root length and low root and rhizome mass, i.e., lower anchoring capacity. To better assess coastal resilience to sea level rise, our findings suggest (i) to include these effect traits in models and experimental analyses of salt marsh vertical accretion and (ii) to consider effects of vegetation roughness on accretion in salt marsh management schemes. Highlights: Above-ground plant traits allow quantifying vegetation roughness. Below-ground plant traits indicate anchoring effects. Salt marsh vertical accretion determined on 335 plots located along the German North Sea coast. Plant traits contribute to predicting positive and negative vertical accretion.